Gross anatomy and morphometry of selected visceral organs of broiler chicken at different age groups - Rani, Ripa; Golbar, Hossain M; Rauf, Shah Md Abdur (Asian Journal of Medical and Biological Research, 2020)
A lot of diseases develop pathognomonic lesions in some visceral organs. It is important to know the normal anatomy, morphometry and color of these visceral organs to find out the changes due to specific diseases during necropsy. Considering these views, the research was planned to make a baseline data on the visceral organs of broiler chickens. A total of 50 broiler with the age of 2 and 4 weeks, 25 in each age groups, were euthanized and liver, lungs, spleen, bursa of Fabricius, and ceca were collected at necropsy. The length, breadth, thickness, weight and volume of each organ were recorded using measuring scale, electric balance and water displacement. The liver was flattened and deep reddish brown in color. The mean weight, length, width and thickness of right and left lobes at the age of 2 weeks were 12.94±1.34 g, 6.0±0.36 cm, 3.20±0.16 cm, 0.62±0.23 cm; and 5.70±0.14 cm, 1.80±0.22 cm and 0.62±0.14 cm, respectively. On the other hand, at 4 weeks they were 43.12±3.61 g, 9.07±0.31 cm, 4.73±0.38 cm, 0.83±0.17 cm; and 7.10±0.29 cm, 3.47±0.20 cm and 0.80±0.14 cm for the right and left lobes, respectively. The lungs were nearly rectangular, unlobed, bright red in color. The mean weight of lungs of 2 and 4 week were 1.94±0.15 g and 8.02±1.09 gm, respectively. The length, width and volume of lungs were 2.27±0.21 cm, 2.30±0.08 cm, 1.57±0.33 cc and 3.30±0.16 cm, 2.43±0.26 cm, 8.00±0.81 cc at the age of 2 and 4 weeks, respectively. The spleen was oval, reddish brown in color. The weight, length and diameter of spleen at 2 weeks were 0.56±0.25 g, 1.40±0.29 cm and 2.63±0.39 cm while those at 4 weeks were 1.90±0.41 g, 1.93±0.14 cm, and 4.10±0.28 cm. The bursa of Fabricius was round, cream colored having a diameter of 3.57±0.17 cm and 3.97±0.16 cm, respectively at 2 and 4 weeks of age. The diameters of left and right cecum at 2 and 4 week of age were 1.93±0.40 cm and 3.10±0.36 cm; 1.97±0.25 cm and 2.87±0.66 cm respectively. Asian J. Med. Biol. Res. September 2020, 6(3): 555-563